Maduku Untuk Diabetesku, Penyuluhan Kesehatan Warga Desa Kalibaru, Tengah Tani, Cirebon: My Honey for My Diabetes, Health Counseling for Kalibaru Villagers, Tengah Tani, Cirebon - Kunaedi, Aan; Susilo, Rinto; Lestari, Trisna; Bachtiar, Arsyad; Milla, Muayyadah; Lediyana, Riska (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
Non-communicable degenerative diseases in Indonesia are increasing. Prevention efforts with herbal and traditional treatments are often and still believed by the community as alternative medicine, as well as the perception of avoiding the side effects of a drug. The current trend of switching herbs and traditional medicine to honey is increasingly rife. Diabetes Mellitus is a chronic metabolic disease characterized by hyperglycemia, as an indicator of reduced body response to insulin as a regulator of sugar metabolism in the body. The implementation method begins with observation to Kalibaru Village Head partners, distribution of activity flyers 1 week before the activity, with implementation on Friday, December 22, 2023 at 08.00-11.00; located at Kalibaru Village hall, Tengah Tani District with official lecturer team participants; STFMC students; Village head, apparatus, village midwife, and Kalibaru villagers. From the results of the activity, there was quite a lot of public interest in the concern of blood sugar checks, there was an active discussion of the audience about counseling and responses to herbal drinks. From 59 respondents, data were obtained on checking glucose levels for 2 hours of fasting for 30 residents <115 mg / dl, 22 residents 116 - 200 mg / dl, 4 residents 201-300 mg / dl, and 3 residents > 300 mg / dl. With counseling activities, it is expected to increase citizens' awareness of health, and the government's synergy efforts in controlling deadly degenerative diseases can be controlled together with all parties.